HUBUNGAN SOCIAL SUPPORT DENGAN RESILIENSI AKADEMIK MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK DI UNIVERSITAS ISLAM BALITAR (UNISBA) BLITAR - Haryanti, Nik; Muspita, Novi Catur; Rohmah, Liatul; Rachmawati, Danar Nanda (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
The purpose of this study is to determine the relationship between social support and academic resilience in undergraduate students at the Islamic University of Balitar (UNISBA) Blitar. This study uses a purposive sample strategy in correlational quantitative research. There are one hundred students who are the sample of this research. Questionnaires are used in the data collection process. using the product moment correlation analysis method with Windows SPSS 22.0. The findings of this study show that social support and academic resilience in female students are positively correlated, meaning that the higher the social support that female students have, the higher the academic resilience. The two-sided significance value (0.000) is greater than the probability of 0.05 (0.000 < 0.05), and the calculated r value is 0.493 > from the table r of 0.210